Desalination of Water: a Review - Darre, Natasha C.; Toor, Gurpal S. (Current pollution reports, 2018)
Purpose of Review In the face of rising water demands and dwindling freshwater supplies, alternative water sources are needed. Desalination of water has become a key to helping meet increasing water needs, especially in water-stressed countries where water obtained by desalination far exceeds supplies from the freshwater sources. Recent Findings Recent technological advancements have enabled desalination to become more efficient and cost-competitive on a global scale. This has become possible due to the  improvement in the materials used in membrane-based desalination, incorporation of energy-recovery devices to reduce electricity demands, and combining different desalination methods into hybrid designs. Further, there has been a gradual phasing-in of renewable energy sources to power desalination plants, which will help ensure the long-term sustainability of desalination. However, there are still challenges of reducing energy demands and managing waste products from the desalination to prevent adverse environmental effects. Summary This article reviews the history, location, components, costs, and other facets of desalination and summarizes the  new technologies that are set to improve the overall efficiency of the desalination process.